Pressure pulsation during the outlet pressure variation process of the pump turbine under operating conditions - Li, Zhenggui; Xu, Lixin; Li, Wangxu; Cheng, Chuanshi; Song, Xiaotong; Jiao, Yanxiong; Jin, Dongbing; Sa, Meiying (International Journal of Agricultural and Biological Engineering, 2025)
This paper studies the flow characteristics of the pump turbine of a pump under operating conditions during the outlet pressure variation process, aiming to improve its operational stability in pumping and compressing air energy storage systems. Through numerical simulations of the flow process, the pressure distribution and pressure pulsation characteristics in key areas such as the volute, double-row impeller, runner, and tailpipe are analyzed in depth. The study reveals that during the outlet pressure variation process under operating conditions, the pressure distribution is directly influenced by the outlet pressure variation, while pressure pulsation is mainly affected by the dynamic and static interference within the unit, with the pressure pulsation amplitude influenced by the rate of pressure variation. The results indicate that during the outlet pressure variation process, it is important to prevent the outlet pressure from staying in unstable working ranges to reduce the intensity of pressure pulsation. A smoother rate of pressure variation should be adopted before stopping the outlet pressure variation to reduce the “pressure variation inertia” and enhance the overall operational stability of the water turbine unit. Key words: pump turbine; outlet pressure variation; pressure pulsation; numerical simulation DOI: 10.25165/j.ijabe.20251802.9266 Citation: Li Z G, Xu L X, Li W X, Cheng C S, Song X T, Jiao Y X, et al. Pressure pulsation during the outlet pressure variation process of the pump turbine under operating conditions. Int J Agric & Biol Eng, 2025; 18(2): 155–164.